Studi Keefektifan Pengembangan Pendidikan Masa Depan - Sri Setyowati, ; M. Arifana, (Pendidikan Dasar, 2004)
Studi keefektifan didalam perkembangan pendidikan masa depan yang ditentukan oleh perhatian para warga sekolah, pendidik, kepala sekolah dan orangtua. Untuk mencapai sekolah efektif diperlukan konsep manajemen berbasis sekolah, untuk menuju pendidikan sekolah masa depan yang efektif.This paper tries to develop a concept corcerning the effectiveness of the development of future education which is determined by the degree of attention given by the stakeholders comprising the teachers, the headmasters, student and parents. And to make the school effective, it is necessary that a School-Based Management be developed.